2005
DOI: 10.1111/j.1365-3040.2005.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring variation in high temperature induced floral bud abortion across Arabidopsis thaliana accessions

Abstract: A system to study the basis of high temperature-induced floral bud abortion using naturally occurring variation for heat-tolerance of floral development among Arabidopsis thaliana (L.) Heynh. wild-collected accessions is described. High temperature-induced floral bud abortion was dependent on both temperature and duration of exposure. Exposing the inflorescence alone to high temperature was sufficient to induce floral bud abortion, and Col-0 and No-0 photosynthetic rates were similar during high temperature ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…Reduced anther elongation upon heat stress has also been found in other species, such as barley (Sakata et al, 2010). The observations of Kim et al (2001) and Warner and Erwin (2005) are in line with our observation that natural variation exists both in terms of duration of the sensitivity window and the degree of reduction in seed set within the sensitivity window. However, comparison of floral stages between different studies should be done carefully since the matching between the developmental regions and the landmark events in flower and seed development are based on generalization and natural variation was observed for the number of flowers that opened per day.…”
Section: Identification Of a Developmental Sensitivity Windowsupporting
confidence: 79%
See 4 more Smart Citations
“…Reduced anther elongation upon heat stress has also been found in other species, such as barley (Sakata et al, 2010). The observations of Kim et al (2001) and Warner and Erwin (2005) are in line with our observation that natural variation exists both in terms of duration of the sensitivity window and the degree of reduction in seed set within the sensitivity window. However, comparison of floral stages between different studies should be done carefully since the matching between the developmental regions and the landmark events in flower and seed development are based on generalization and natural variation was observed for the number of flowers that opened per day.…”
Section: Identification Of a Developmental Sensitivity Windowsupporting
confidence: 79%
“…In addition, a sensitive period at floral stage 12 was identified (Kim et al, 2001). A more extensive study in Arabidopsis, investigating floral bud abortion upon heat stress in 13 natural accessions, demonstrated that in the Columbia accession floral stage 12, but not floral stage 9, was most sensitive (Warner and Erwin, 2005). That floral stage 9 was not identified could be caused by the longer period of heat that was applied (36°C for 72 h).…”
Section: Identification Of a Developmental Sensitivity Windowmentioning
confidence: 99%
See 3 more Smart Citations